Cross-sectional and longitudinal associations of serum Cysteine-rich 61 with severity and prognosis among community-acquired pneumonia patients in China - Yao, Meng-Xing; Cheng, Jia-Yi; Liu, Ying; Sun, Jing; Hua, Dong-Xu; He, Qi-Yuan; Liu, Hong-Yan; Fu, Lin; Zhao, Hui (Frontiers in Medicine, 2022)
Background：Cysteine-rich 61 (CYR61) is implicated in many pulmonary diseases. However, the relationship of CYR61 and community-acquired pneumonia (CAP) patients was unknown. This research aimed to estimate the correlations between serum CYR61 with severity and prognosis in CAP patients through a prospective cohort study. Methods: All 541 CAP patients were enrolled. Fasting venous blood was collected. Clinical characteristics and demographic information were obtained. CYR61 and inflammatory cytokines were detected in serum using ELISA. Results: Serum CYR61 was gradually risen in parallel with severity scores in CAP patients. Correlative analysis indicated that serum CYR61 was strongly associated with many clinical parameters in CAP patients. Moreover, mixed logistic and linear regression models found that there were positive correlations between serum CYR61 and CAP severity scores after adjusted for age, BMI and respiratory rate. Stratified analyses suggested that age affected the associations between serum CYR61 and severity scores. On admission, serum higher CYR61 elevated the risks of mechanical ventilation, vasoactive agent, ICU admission, death and longer hospital stays during hospitalization. Moreover, serum CYR61 in combination with severity scores upregulated the predictive capacities for severity and death than single serum CYR61 or severity scores in CAP patients. Conclusion: There are significantly positive dose-response associations between serum CYR61 on admission with the severity and adverse prognostic outcomes, demonstrating that CYR61 is involved in the pathophysiology of CAP. Serum CYR61 may be used as a potential biomarker for diagnosis and prognosis in CAP patients.